2003
DOI: 10.1016/s1534-5807(03)00274-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Modulation of PPARγ Phosphorylation Regulates Insulin Sensitivity

Abstract: Obesity-associated diabetes is epidemic in industrialized societies. The nuclear receptor peroxisome proliferator-activated receptor gamma (PPARgamma) is highly expressed in adipose tissue and the presumed molecular target for antidiabetic thiazolidinedione drugs that reverse insulin resistance but also promote weight gain. Phosphorylation reduces the activity of PPARgamma in vitro, but physiological relevance has not been demonstrated. We have studied mice homozygous for a mutation (S112A) that prevents PPARg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
157
2
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(172 citation statements)
references
References 46 publications
11
157
2
2
Order By: Relevance
“…Another regulatory covalent modification of PPARg is phosphorylation at Ser-112 by mitogen-activated protein kinases (MAPKs) such as p44/p42 (ERKs 1 and 2) and c-Jun amino-terminal kinase (JNK), which results in transcriptional inactivation of PPARg (Camp and Tafuri 1997). Although it is widely accepted that phosphorylation of PPARg2 inhibits its activity, a point mutation at Ser-112 does not disrupt the ability of PPARg2 to confer adipogenesis (Rangwala et al 2003). However, in vivo studies have shown that PPARg2 phosphorylation at this residue modulates insulin sensitivity in the setting of diet-induced obesity (Rangwala et al 2003).…”
Section: Ppargmentioning
confidence: 99%
See 1 more Smart Citation
“…Another regulatory covalent modification of PPARg is phosphorylation at Ser-112 by mitogen-activated protein kinases (MAPKs) such as p44/p42 (ERKs 1 and 2) and c-Jun amino-terminal kinase (JNK), which results in transcriptional inactivation of PPARg (Camp and Tafuri 1997). Although it is widely accepted that phosphorylation of PPARg2 inhibits its activity, a point mutation at Ser-112 does not disrupt the ability of PPARg2 to confer adipogenesis (Rangwala et al 2003). However, in vivo studies have shown that PPARg2 phosphorylation at this residue modulates insulin sensitivity in the setting of diet-induced obesity (Rangwala et al 2003).…”
Section: Ppargmentioning
confidence: 99%
“…Although it is widely accepted that phosphorylation of PPARg2 inhibits its activity, a point mutation at Ser-112 does not disrupt the ability of PPARg2 to confer adipogenesis (Rangwala et al 2003). However, in vivo studies have shown that PPARg2 phosphorylation at this residue modulates insulin sensitivity in the setting of diet-induced obesity (Rangwala et al 2003). Recent studies have revealed that CDK5 phosphorylates PPARg at Ser-273 to attenuate PPARg trans-activation of important adipocyte genes, including adiponectin (Choi et al 2010).…”
Section: Ppargmentioning
confidence: 99%
“…Indeed, over-expression of a phosphorylation defective PPAR mutant (in which serine 112 is mutated to alanine [PPAR S112A]) in mouse NIH-3T3 fibroblasts or 3T3-L1 pre-adipocytes results in enhanced adipogenesis compared with wild-type protein [12,35]. In vivo, homozygous PPAR S112A knock-in mice are protected from high-fat diet-induced insulin resistance and display decreased adipocyte size, elevated serum adiponectin, and reduced FFA levels [36]. PPAR also undergoes sumoylation at lysine 107 in the AF1 and lysine 395 A c c e p t e d M a n u s c r i p t 8 in the AF2 region [37].…”
Section: Page 7 Of 25mentioning
confidence: 99%
“…Heterozygous PPAR␥-deficient mice are protected from high-fat diet-induced weight gain and loss of insulin sensitivity (9). Mice homozygous for a constitutively active form of PPAR␥ resulting from an S112A mutation (mouse S112 is equivalent to human S114) gain weight normally and are protected against obesity-induced insulin resistance (10). Mice with a mutation equivalent to the human P467L mutation maintain normal insulin sensitivity with altered body fat distribution and mild hypertension (11).…”
mentioning
confidence: 99%